Investigate and educate from the museum of contemporary art - Juan David Quintero Arbeláez; Carolina Mejía Romero (Corporación Universitaria Minuto de Dios, 2011)
This paper talks about the stake and lines of action in which the Museum of Contemporary Art of Uniminuto works regarding education and research. It presents the Museum as a promoter of experiences to stimulate the artistic and social development of the community. The text also mentions that these processes must be integrated with the real context of the community in order to have a great impact and challenge in their tasks. The intention with the community and the spreading of its heritage make part of an integral educational role of the museum. The most important tools from this project are the education and research in order to promote a sense of belonging, responsibility, own criteria and personal development in the community.